2020
DOI: 10.1080/02601370.2020.1790050
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge-oriented and relationship-oriented roles of popular education in labour movement parties in Sweden

Abstract: Political parties are essential for the functioning of parliamentary democracy, yet parties have not received much attention in contemporary research on popular education. The aim of this article is to analyse the contemporary role of party-political education as a form of popular education in two labour movement parties in Sweden. The study is based on semi-structured interviews focusing on the reasoning behind the organisation of education in political parties. The interviews were conducted with ten intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 18 publications
0
10
0
9
Order By: Relevance
“…Historiallisesti tarkasteltuna vapaalla kansansivistystyöllä on ollut merkittävä rooli poliittisen koulutuksen tarjoajana luottamustehtäviin ja vaikuttajiksi pyrkiville kansalaisille. Viitteitä löytyy, että yhteydet sivistystyön ja poliittisten puolueiden välillä olisivat elinvoimaisia Ruotsissa vielä tänä päivänä (Nordvall & Malmström 2015;Nordvall & Pastuhov 2020). Suomen osalta ei ole vastaavanlaisia tutkimuksia.…”
Section: Johdantounclassified
See 2 more Smart Citations
“…Historiallisesti tarkasteltuna vapaalla kansansivistystyöllä on ollut merkittävä rooli poliittisen koulutuksen tarjoajana luottamustehtäviin ja vaikuttajiksi pyrkiville kansalaisille. Viitteitä löytyy, että yhteydet sivistystyön ja poliittisten puolueiden välillä olisivat elinvoimaisia Ruotsissa vielä tänä päivänä (Nordvall & Malmström 2015;Nordvall & Pastuhov 2020). Suomen osalta ei ole vastaavanlaisia tutkimuksia.…”
Section: Johdantounclassified
“…Esimerkiksi ruotsalaisten vasemmistopuolueiden koulutusta valottavassa tutkimuksessa esitetään, että uusien jäsenten koulutuksissa luodaan yhteenkuuluvuutta, mutta ilman varsinaista poliittista vakuuttamista, sillä jäsenten oletetaan jo omaksuneen puolueen ideologiset lähtökohdat (Arriaza Hult 2020). Toisessa tutkimuksessa on todettu työväen sivistystyöllä olevan Ruotsissa sekä tietoon että yhteisöllisyyteen liittyviä rooleja (Nordvall & Pastuhov 2020). Nämä roolit liittyvät toisaalta ideologiseen koulutukseen ja jäsenistön osaamisen kehittämiseen, kuten järjestötaitoihin, toisaalta verkostoitumiseen ja puoluehierarkiassa etenemiseen.…”
Section: Aiempaa Tutkimustaunclassified
See 1 more Smart Citation
“…The most compelling results of this research show how the motives for participation have, since the 1990s, been linked to personal spare-time interests and desires to gain knowledge through encounters with others. This does not exclude the prevalence of study circles with specific political orientation; for example, when political parties organise studies in cooperation with study associations (Nordvall & Pastuhov, 2020). However, this type of explicitly political popular education constitutes a limited part of the total number of study circles.…”
Section: Study Circles In Relation To Democracy and Inclusionmentioning
confidence: 99%
“…In the Nordic countries, there are strong links between diverse political and religious movements and the tradition of popular education (Lövgren, 2015;Nordvall & Fridolfsson, 2019). Correspondingly, research concerned with the democratic and political role of popular education have shown an interest in the link between specific social movements and their use of popular education (Arvidson 1985;Gustavsson 1991;Nordvall & Pastuhov, 2020). Even though critics have argued that this link to social movements has become far weaker than what is often assumed in both political and academic discourse on Nordic popular education (Manninen, 2017;Sundgren, 1999), it is still a point of departure when the role of popular education is discussed.…”
Section: Introductionmentioning
confidence: 99%